ASSESSMENT OF SEGREGATING GENERATIONS FOR GENETIC VARIABILITY AND YIELD REGULATING TRAITS IN MUNGBEAN - HEMANT SAHU,; JAIRAM AMADABADE,; PRAFULL KUMAR,; ABHINAV SAO, (The Bioscan, 2014)
Looking for limited genetic variation, due to homogeneity and homozygosity, F5 and F6 populations of thirty five mungbean (Vigna radiata L. Wilezek) genotypes were studied to assess genotypic variability and character association considering nineteen nitrogen fixing and yield attributing parameters. Straw protein content (0.306*), nitrogen fixation (0.342*), plant height (0.474*), pod per plant (0.388*), 100 seed weight (0.442*) were found to be major yield factors. Nitrogen fixation had positive and significant correlation with primary branches, seed per pod, yield per plant and straw protein in both the generations. Maximum direct positive effects towards yield were exerted by nitrogen fixing per plant (1.111), seeds per pod (0.423), pods per cluster (0.837), 100-seed weight (0.561) and plant height (0.257). Variability coefficients exhibited approximate similar pattern for both generations indicating stabilization of parameters with generation advance. However, continued recombination was also apparent for GCV and PCV in nodule volume (75.50 and 80.80%), nodule dry weight (43.72 and 48.78%) and nitrogen fixing ability (43.8 and 48.80%) which is probable sign of genetically complex mechanism. The findings will be useful for broadening the genetic base of autogamous crops and establishment of selection criteria for pulse improvement.